2022
DOI: 10.3390/app12020852
|View full text |Cite
|
Sign up to set email alerts
|

On the Detection Capabilities of Signature-Based Intrusion Detection Systems in the Context of Web Attacks

Abstract: Signature-based Intrusion Detection Systems (SIDS) play a crucial role within the arsenal of security components of most organizations. They can find traces of known attacks in the network traffic or host events for which patterns or signatures have been pre-established. SIDS include standard packages of detection rulesets, but only those rules suited to the operational environment should be activated for optimal performance. However, some organizations might skip this tuning process and instead activate defau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(5 citation statements)
references
References 41 publications
0
4
0
1
Order By: Relevance
“…Taha et al [8] reviewed the different anomaly detection methods for categorical data. Diaz Verdejo et al [5] proposed an efficient alternative approach, named signature-recognition-based detection, in the context of web attacks. Mazarbhuiya et al [13] introduced a neighborhood rough-set-based classification approach to detect the anomaly in a mixed attribute dataset.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Taha et al [8] reviewed the different anomaly detection methods for categorical data. Diaz Verdejo et al [5] proposed an efficient alternative approach, named signature-recognition-based detection, in the context of web attacks. Mazarbhuiya et al [13] introduced a neighborhood rough-set-based classification approach to detect the anomaly in a mixed attribute dataset.…”
Section: Related Workmentioning
confidence: 99%
“…Anomaly-based IDS is the name given to the ensuing system [3,4]. However, a signature-recognition-based intrusion detection technique [5] uses a database of known attack signatures and raises an alarm whenever network traffic matches any signature. Usually, a computer and associated network can easily use an anomaly-based IDS as a risk mitigation technique.…”
Section: Introductionmentioning
confidence: 99%
“…Diaz-Verdejo Jesus et al conducted experimental studies on the detection rates of three standard pre-configurations of SIDS in the context of URI web attacks and proposed an effective method to reduce false positives by disabling complete rule sets of signatures. However, WAF is only a subset of the detection capabilities of SIDS, and it is unclear whether their model results hold true in different types of attacks [4]. Saez-de-Camara Xabier et al found that traditional IT security mechanisms, such as signature-based intrusion detection and defense systems, are difficult to integrate [5].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to traditional fields of application of information systems, attacks on critical infrastructure facilities, which include energy companies, can lead to catastrophic consequences. Therefore, methods of detecting malicious activity, based on the use of signatures that ensure mathematically strict recognition, do not lose their relevance in the creation of cybersecurity systems, such as network intrusion detection systems (NIDS), antiviruses, anti-worm systems and spam filters [1,2].…”
Section: Introductionmentioning
confidence: 99%